PERAN CUSTOMER SATISFACTION MEMODERASI PENGARUH RELATIONSHIP MARKETING TERHADAP CUSTOMER LOYALTY (Studi pada PT. Bank BRI Cabang Gatot Subroto Denpasar) - Parsana, Dewa Nyoman Wiesdya Danabrata; Giantari, I Gusti Ayu Ketut (E-Jurnal Manajemen, 2020)
The purpose of this study is to explain the effect of customer satisfaction and relationship marketing on customer loyalty and to explain customer satisfaction moderating the effect of relationship marketing on customer loyalty at PT. Bank BRI Branch Gatot Subroto Denpasar. This research was conducted at PT. Bank BRI Branch Gatot Subroto Denpasar. The study population was all customers of PT. Bank BRI Branch Gatot Subroto Denpasar. Sampling using a purposive sampling method. The data analysis technique used is MRA. The results showed that relationship marketing and customer satisfaction had a positive and significant effect on customer loyalty at PT. Bank BRI Branch Gatot Subroto Denpasar. Customer satisfaction moderates the positive effect of relationship marketing on customer loyalty at PT. Bank BRI Branch Gatot Subroto Denpasar. The research implications show that customer relationship marketing and customer satisfaction to date can be categorized as good, but management must try to give the best to customers in order to maintain and increase customer loyalty. Keywords: customer satisfaction, relationship marketing, customer loyalty